Analisis Bibliometrik : Fokus penelitian hasil belajar dalam pembelajaran matematika (2013-2023) - Narayani, Daliyah; Zulfah; Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this bibliometric analysis is to see the opportunities and development of research trends related to learning outcomes in mathematics learning. The method used is bibliometrics by collecting article data from 2019-2023 through the Google Scholar site with the Publish or Perish 1,000 journal software. The results showed the most publications in 2022 as many as 109. Variables related to learning outcomes in mathematics learning that have opportunities and novelty to be researched in the future are pbl and teachers